Exercise and Arterial Stiffness in the Elderly: A Combined Cross-Sectional and Randomized Controlled Trial (EXAMIN AGE) - Deiseroth, Arne; Streese, Lukas; Köchli, Sabrina; Wüst, Romy Sandra; Infanger, Denis; Schmidt-Trucksäss, Arno; Hanssen, Henner (Frontiers in Physiology, 2019)
Introduction: Arterial stiffness (AST) is a main determinant of cardiovascular (CV) mortality. Long-term physical activity (PA) is considered to decrease age-related progression of AST but effects of short-term exercise interventions on AST remain unclear. Methods: In a combined cross-sectional and interventional study approach, we investigated the effects of long-term PA and short-term high-intensity interval training (HIIT) on AST in an older population. 147 older individuals (mean age 59±7 years) were assigned to three groups according to their PA and CV risk profile and compared: healthy active (HA, n=35), healthy sedentary (HS, n=33) and sedentary at risk (SR, n=79). In addition, SR were randomized to either 12 weeks of HIIT or standard recommendations. Pulse wave velocity (PWV) was measured by applanation tonometry. Cardiorespiratory fitness (CRF) was performed by symptom-limited spiroergometry to determine maximal oxygen uptake (VO2max). Results: Higher CRF was associated with lower PWV (p<0.001) and VO2max explained 18% of PWV variance. PWV was higher in SR (8.2±1.4 m/s) compared to HS (7.5±1.6 m/s) and HA (7.0±1.1 m/s; p<0.001). 12 weeks of HIIT did not change PWV in SR. HIIT-induced reduction in systolic BP was associated with a reduction in PWV (p<0.05). Discussion: SR show higher PWV compared to HS and long-term PA is associated with lower PWV. Reduction of AST following short-term HIIT seems to depend on a concomitant decrease in blood pressure. Our study puts into perspective the effects of long- and short-term exercise on arterial wall integrity as treatment options for CV prevention in an older population. Clinical Trial Registration: ClinicalTrials.gov: NCT02796976 (https://clinicaltrials.gov/ct2/show/NCT02796976)